Intra-Household Labour Allocation, Migration, and Remittances in Rural El Salvador - Acosta, Pablo (Taylor and Francis, 2020)
Migration can affect labor participation decisions back home, either by stimulating work to replace foregone labor, or reducing it through the role of remittances. Using evidence from a rural panel for El Salvador with a comprehensive module on agricultural income shocks, this study finds that migration and remittances generate only minor labor reallocation effects within households. Contradicting previous evidence based on cross section data, no impact is registered for off-farm labor supply. However, remittances and migration tend to increase female participation and hours worked in agricultural activities, and reduce time dedicated to off-farm and domestic activities. No major effects are found on self-employment.